Reduction of Serious Adverse Events Demanding Study Exclusion in Model Development: Extracorporeal Life Support Resuscitation of Ventricular Fibrillation Cardiac Arrest in Rats. Issue 6 (December 2016) - Warenits, Alexandra-Maria; Sterz, Fritz; Schober, Andreas; Ettl, Florian; Magnet, Ingrid Anna Maria; Högler, Sandra; Teubenbacher, Ursula; Grassmann, Daniel; Wagner, Michael; Janata, Andreas; Weihs, Wolfgang
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Extracorporeal life support is a promising concept for selected patients in refractory cardiogenic shock and for advanced life support of persistent ventricular fibrillation cardiac arrest. Animal models of ventricular fibrillation cardiac arrest could help to investigate new treatment strategies for successful resuscitation. Associated procedural pitfalls in establishing a rat model of extracorporeal life support resuscitation need to be replaced, refined, reduced, and reported. Anesthetized male Sprague-Dawley rats (350–600 g) (n = 126) underwent cardiac arrest induced with a pacing catheter placed into the right ventricle via a jugular cannula. Rats were resuscitated with extracorporeal life support, mechanical ventilation, defibrillation, and medication. Catheter and cannula explantation was performed if restoration of spontaneous circulation was achieved. All observed serious adverse events (SAEs) occurring in each of the experimental phases were analyzed. Restoration of spontaneous circulation could be achieved in 68 of 126 rats (54%); SAEs were observed in 76 (60%) experiments. Experimental procedures related SAEs were 62 (82%) and avoidable human errors were 14 (18%). The most common serious adverse events were caused by insertion or explantation of the venous bypass cannula and resulted in lethal bleeding, cannula dislocation, or air embolism. Establishing an extracorporeal life support model in rats has confronted us with technical challenges. Even advancements in small animal critical care management over the years delivered by an experienced team and technical modifications were not able to totally avoid such serious adverse events. Replacement, refinement, and reduction reports of serious adverse events demanding study exclusions to avoid animal resources are missing and are presented hereby.